Synthesis, characterization and electrical properties of hybrid mono-iron-substituted undecatungstosilicate/(Bi, Pb)-2223 phase superconductors. (4th October 2019) - El Ghouch, Nour; Al-Oweini, Rami; Awad, R
Abstract: A conventional solid-state reaction technique was used to synthesize superconducting samples of (Bi1.8 Pb0.4 )Ca2 Sr2 Cu3 O10+ δ, (Bi, Pb)-2223, phase. The electrical properties of (Bi, Pb)-2223 samples were investigated upon the addition of different amounts of ferratoundecatungstosilicate (K5 [SiFe(OH2 )W11 O39 ]·14H2 O, FeSiW11 ) nanoparticles, x, ranging from 0.00 to 0.20 wt%. The optimum preparation conditions to obtain high quality superconducting bulk samples were considered. The average particle size of these antiferromagnetic nanoparticles was approximately 19.56 nm. Such Fe-containing polyoxometalates are a highly interesting class of inorganic nanomaterials, possessing outstanding properties of high oxidation states as well as thermal and oxidative stability. Consequently, the superconducting samples were characterized by powder x-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDX) to study the structure, morphology and elemental composition of the prepared samples, respectively. The volume fraction of the (Bi, Pb)-2223 phase was improved by the nano-addition, while the lattice parameters showed unchangeable values. On the other hand, the superconducting electrical parameters were assessed via dc electrical resistivity and critical current density measurements. The obtained results indicated that the addition of nano FeSiW11 enhanced the superconducting transition temperature (Tc ) and the transport critical current density (Jc ) up to x = 0.16 and 0.12 wt%, respectively. Conversely, Tc and Jc were suppressed with further increases of nanoparticle addition.